Enhanced temperature stability of ferroelectric properties in lead-free (1−x)(Bi0.5Na0.4K0.1)TiO3-x(Ba0.5Sr0.5)TiO3 solid solutions. Issue 24 (15th December 2022) - Zhao, Mo; Zhang, Leiyang; Huang, Yunyao; Yan, Yangxi; Gao, Jinghui; Du, Hongliang; Jin, Li
Abstract: With its complicated composition architecture, (Bi0.5 Na0.5 )TiO3 (BNT)-based relaxor ferroelectrics exhibit distinctive dielectric relaxation phenomena and attractive characteristics. The structural, dielectric, and ferroelectric characteristics of (1– x )(Bi0.5 Na0.4 K0.1 )TiO3 - x (Ba0.5 Sr0.5 )TiO3 (BNKT- x BST) solid solutions with x  = 0–0.4 were thoroughly examined in this study. The x  = 0.1 and 0.2 versions exhibited unexpected ferroelectricity enhancement, and the depolarization temperatures and ferroelectric-relaxor transition temperature were both increased compared to that of the BNKT undoped sample. This enhancement is due to the creation of a tetragonal ferroelectric phase after the introduction of a moderate BST member, according to room temperature and temperature-dependent x-ray diffraction data. The characterization of ferroelectric properties indicated that ferroelectricity was enhanced by increasing the rapidly declining temperatures for the remnant polarization and coercive field, compared to those of the BNKT undoped sample. This discovery contributes to a better understanding of the relationship between the structure and properties of complex relaxor ferroelectrics. A phase diagram of the BNKT- x BST solid solution is also provided, which can be used to guide the search for specific lead-free functional materials for the capacitors, actuators, and transducers based on this eco-friendly system.